1999
DOI: 10.1023/a:1018791622441
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The following study examined the association between neurocognitive performance and emotional status in chronic pain patients. Seventy-three chronic pain patients recruited consecutively from services in a general medical hospital completed a battery of 10 neurocognitive measures and the Symptom Checklist-90-Revised (SCL-90-R; a gross measure of emotional distress). Cluster analytic procedures were used to identify a three-cluster group solution based on the SCL-90-R. Results indicate that subjects highest in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The extent to which our results suggest an inability to process monetary risk specifically, and in turn reflect a dysfunctional reward system in CBP, needs discussion. This is because reward perception and action may also be altered by an overall lack of or difference in emotional awareness during decisions [ 47 ] or by changes in attentional mechanisms [ 48 , 49 ]. Importantly, both of these alternatives might be due to our participants either having a history of chronic pain, which would affect the brain’s circuitry, and/or having a presence of pain while they are performing the task, which might change their scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent to which our results suggest an inability to process monetary risk specifically, and in turn reflect a dysfunctional reward system in CBP, needs discussion. This is because reward perception and action may also be altered by an overall lack of or difference in emotional awareness during decisions [ 47 ] or by changes in attentional mechanisms [ 48 , 49 ]. Importantly, both of these alternatives might be due to our participants either having a history of chronic pain, which would affect the brain’s circuitry, and/or having a presence of pain while they are performing the task, which might change their scores.…”
Section: Discussionmentioning
confidence: 99%
“…This leads us to the second possibility mentioned above – that changes in attentional mechanisms or resources might be contributing to changes in connectivity and differences in behavior. Due to the overlap in the network regions involved in both chronic pain and reward, it is possible that the cognitive demand of the ongoing background pain may alter CBP patients’ ability to attend to the task (in this case, to attend to both losses and gains equally) [ 48 , 49 ], and in turn this may be reflected in our neuroimaging findings. Previous results have shown that CBP patients do not appear to have deficits in other types of tasks, including those measuring attention and short-term memory [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain has been associated with cognitive problems in the domains of memory, concentration, problem solving, abstract thinking, and cognitive efficiency 1-3 . Most evidence related to the adverse effect of pain on cognitive functioning is derived from chronic pain patients, including those with fibromyalgia, whiplash, arthritis and other chronic pain conditions 4-7 .…”
Section: Introductionmentioning
confidence: 99%
“…First, patients with chronic pain complain of significant memory disturbances [15]. These complaints have been verified in standardised neurocognitive assessments of teenage, adult and elderly chronic pain patients across a range of chronic pain-causing conditions, and the severity of impairment is proportional to the degree of pain experienced at assessment [618]. Second, experimentally inducing pain in otherwise healthy volunteers interferes with memory function if the painful stimulus is applied during encoding and/or retrieval in long-term memory tasks [1821].…”
Section: Introductionmentioning
confidence: 99%